KOMPARASI GEOPORTAL KOTA DI INDONESIA DENGAN GEOPORTAL KOTA DI EROPA (STUDI KASUS GEOPORTAL KOTA PAYAKUMBUH DAN GEOPORTAL KOTA PARIS) - Ferriansyah, Andri; Yulfa, Arie (JURNAL BUANA, 2024)
This research aims to find out comparative information about the Payakumbuh City geoportal in Indonesia with the Paris City geoportal in France, challenges in managing data and metadata in the Payakumbuh City geoportal and the impact of utilizing the Payakumbuh City geoportal on city governance. The type of research is qualitative with a comparative descriptive approach. Data collection using interview and observation techniques. The results showed that the Payakumbuh City geoportal has shortcomings in the availability of data and metadata than the Paris City geoportal and the producer agencies that have not produced data are still more than the City of Paris which has agencies that are active in data production, and in data accessibility and the features and functions provided are still relatively few than the Paris City geoportal. The management of data availability and metadata has challenges in producer agencies as the main providers of data in the Payakumbuh City geoportal and the utilization of the Payakumbuh City geoportal for city governance, decision making and public services has had a good impact on the Payakumbuh City government.